An analytical study on the bending moment acting on the girder of a long-span cable-supported bridge suffering from cable failure. (15th July 2018) - Shoghijavan, Mohammad; Starossek, Uwe
Highlights: Based on a conceptual bridge model, an analytical method is developed. An approximation function is proposed to calculate the bending moment on the girder. The least squares method is used to minimize the error of the approximation function. Larger stiffness ratio leads to larger bending moment on the girder due to cable loss. Abstract: In this study, the structural behavior of a long-span cable-supported bridge after the sudden rupture of one of its axial cables is of concern. Cable failure produces large bending moments on the girder of the bridge. Henceforth, the focus of this study is to find the "maximum bending moment" on the girder due to the cable failure. For this purpose, an analytical approach based on differential equations of the system will be used. Then, an approximation function for a simplified bridge model in a cable-loss scenario will be derived. The use of the least squares method is also applied to minimize the error of the approximation function. The proposed approximation function has been checked by numerical models, and its good accuracy has been proven. The results show that by increasing the ratio of the bending stiffness of the girder to the axial stiffness of the cables, cable failure produces a larger bending moment on the girder.